The Effect of Giving Semi Fowler Position in Reducing Ineffective Breathing in Chronic Kidney Disease (CKD) Patients at RSUD Ibnu Sina Gresik Hospital (Case Study Research) - Nur Soemah, Eka; Savinda Afista; Agus Haryanto (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Chronic kidney disease is a condition where the kidneys fail to perform their function to excrete substances that are not needed by the body, resulting in accumulation in the body which can trigger uremia. This scientific work aims to apply nursing care to CKD patients with ineffective breathing patterns at Ibnu Sina Gresik Hospital. The method applied in the preparation of this scientific work is the case study method. The subjects in this scientific work are participants with CKD cases and have problems with ineffective breathing patterns who are undergoing treatment at Ibnu Sina Gresik Hospital. Data collection using interview techniques, observation, physical examination, and documentation and was carried out in the period January to March 2023. The nursing care process for participants was carried out for 5 days, and the assessment results were obtained, namely shortness of breath. The implementation process is carried out in accordance with nursing care planning, one of which is by giving the semi-fowler position. A thorough evaluation was carried out during the provision of nursing care, and it was found that the participants with the problem of ineffective breathing patterns were resolved. Participants do not complain of shortness of breath, breathing frequency improves or is in the normal range, dyspnoea decreases, and there is no use of breathing muscles. The problem of ineffective breathing patterns is resolved by the application of nursing care that is carried out comprehensively. Giving the semi fowler position has an impact on reducing ineffective breathing patterns, because in a tilt angle of 45 degrees and applied during treatment is able to press the diaphragm down so that the lungs can expand and get maximum oxygen supply. Keywords: Chronic Kidney Disease, Ineffective Breathing Pattern, Semi-Fowler's Position.